Efficacy of bio-composted agricultural wastes and biocontrol agents in improving soil fertility and controlling dry root rot in King mandarin (Citrus nobilis) orchards - Chau, Anh Thy Thi; Nguyen, Ngoc Thanh; Tat, Anh Thu; Vo, Guong Thi (Agriculture and Natural Resources, 2025)
Importance of the work: Intensification of King mandarin cultivation has been threatened by dry root rot (DRR) disease, causing unsustainable growth of this citrus fruit. Objectives: To evaluate the efficiency of bio-fertilizers (BF) in combination with different bio-control agents on improving soil properties and controlling DRR disease in King mandarin orchards. Materials and Methods: Rice straw waste material was composted with isolated fungi from King mandarin orchards and rice fields. Five treatments were conducted in a complete randomized design: 1): common farmer practice (the control); 2): recommended inorganic fertilizers (RIF); 3): RIF plus BF inoculated with Trichoderma asperellum (BF1); 4): RIF plus BF inoculated with Gongronella butleri (BF2); and 5): RIF plus BF inoculated with Trichoderma sp. from a commercial source (BF3). Results: BF amendment led to significant increases in soil organic matter, soil pH, labile nitrogen, available phosphorus and exchangeable potassium compared to the control with its high dose of inorganic fertilizers. There was a significantly lower density of Fusarium solani and DRR suppression (40–82.5%) as result of BF amendment, with BF plus isolated Trichoderma and Gongronella butleri being the most effective treatment. Consequently, in the second year harvest, fruit yield increased by about 3.5 times that of the control treatments (p < 0.05). Main finding: Using rice straw as waste material to make bio-compost with isolated strains of native fungi could be an optimal practice for improving soil fertility and soil suppression to reduce DRR and enhance fruit yield, promoting an eco-friendly system in King mandarin orchards.